Verification of New Washover Formula with Field Measurements Data - DONNELLY, Chantal; TANAKA, Hitoshi; NGUYEN, Xuan Tinh; LARSON, Magnus (PROCEEDINGS OF COASTAL ENGINEERING, JSCE, 2008)
Prediction of overwash occurrence can provide valuable planning information for local authorities, emergency services, and coastal residents. Based on those proposes a new empirical formula for predicting deposited washover volume was derived. The new formula was developed by modifying the assumptions of previous empirical models using new assump-tions based on the governing physical processes by taking into account the excess runup height over the beach crest and the duration of the overwash event. The empirical coefficient was calibrated using field data sets from United States. Verification of the model with a further fourteen field data sets was shown that the formula yields predictions are comparable to the measured field data with most of predicted overwash volumes falling within a factor of two.